INOVASI “AYAH HEBAT” MELALUI PROGRAM KAMPUNG KB DI KELURAHAN AIR DINGIN - Desi Muslimah; Geovani Meiwanda (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT The “Ayah Hebat” innovation is an innovation program in the KB village. This ayah hebat program is in the Toddler Family Development (BKB) group. This innovation begins to empower fathers who have an important role in a family, making a